Building AI Applications with ChatGPT APIs : master ChatGPT, Whisper and DALL-E APIs by building ten innovative AI projectsl - Yanev, Martin (Packt Publishing Ltd., 2023)
"With best practices, tips, and tricks for building applications using the ChatGPT API, this book is for programmers, entrepreneurs, and software enthusiasts. Python developers interested in AI applications involving ChatGPT, software developers who want to integrate AI technology, and web developers looking to create AI-powered web applications with ChatGPT will also find this book useful. A fundamental understanding of Python programming and experience of working with APIs will help you make the most of this book."--Provided by publisher